Jenis-jenis Progestin dalam Preparat Kontrasepsi - Prilly Astari (PT Kalbe Farma Tbk., 2024)
Progestin plays an important role in contraception. Different types of progestins available have different progesteronic potentials and various effects. However, they have a similar mechanism of action. Each progestin has a certain pattern of partial effects, which can be utilized according to patient’s conditions.